Analysis of Red Onion Supply (Allium Ascalonicum L.) In Sumenep District - Fatmawati; Moh. Kurdi (Agricultural Science, 2019)
This study was conducted to determine the factors that affect the supply of onion, such as onion price factors, prices of onion seeds, the total acreage of production factors, and the supply elasticity of onion. Location research done by purposive, although not Sumenep onion production center in East Java, but Sumenep has the potential for the development of onion production with planting area 429.99 ha, with production quantities 5258.89 tons and productivity levels 12, 23 tons/ha. The method used in this research is quantitative data analysis. Based on the test results simultaneously (together) this indicates that the observed variables are the variable price of onion (Hb), the variable cost of seed onions (HBB), variable production number (Prod), and variable acreage (La) together are very significant to the offer of onion (Qs) in Sumenep. For the partial test results (one by one), the variable price of onion (Hb) is very significant to the offer of onion (Qs) at an error rate of 5% and a rate of 1% mistake. As for the variable production number (Prod) individually at 5% significant real impact on red onions deals (Qs) in Sumenep. For the variable price of seed onions (HBB) and variable acreage (La) did not significantly affect red onion deals (Qs) in Sumenep. Based on the results of the analysis of the supply elasticity of onion in Sumenep of 2018 s / d in 2019 is equal to 0,